Self-Healing Representation in Song Lyrics: Social Semiotics Study of Hitam Putih Album by Feby Putri - Genstar, Veni; Ahmad, Harun; Muliyono, Nurwakhid; Nugrahani, Ari (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Music has long been recognized as an effective medium for conveying human emotions and thoughts. Through song lyrics, music not only serves as a means of self-expression but also conveys profound meaning to those who listen to it. Recently, it has become increasingly common for singers to incorporate themes of self-healing into their music. One such artist is Feby Putri in her second album titled Hitam Putih. The lyrics of these songs present several phenomena of self-healing that are particularly intriguing when examined through the lens of Social Semiotics. Therefore, this study aims to (1) analyze the representation of self-healing in the lyrics of Feby Putri’s Hitam Putih album, and (2) identify the elements of social semiotics used in Feby Putri’s Hitam Putih album. The method used is descriptive qualitative analysis of the text. The techniques employed include documentation and literature review. Additionally, the data analysis technique selected uses a social semiotics approach, where the analysis stages include identifying symbols within the song lyrics. The analysis process began with a thorough reading of the song lyrics, followed by an analysis of the symbols based on the social semiotics framework, then an interpretation of meaning by linking the symbols to the social context. Finally, the symbols were integrated with social semiotics theory to conclude the representation of self-healing in the lyrics. The results of this album’s research reflect the emotional journey of individuals in facing suffering, self-reflection, and the process of finding inner peace. The lyrics in the Hitam Putih album contain representations of deep emotional experiences, reflecting interpersonal relationships between the singer and the listener through empathetic and personal word choices, and structured in a way that supports cohesive and coherent meaning connections.